Evaluating the Employee Engagement Scale through confirmatory factor analysis in Thai local administration settings - Waiphot Kulachai (Cogent Social Sciences, 2024)
This study performs a comprehensive evaluation of the ISA Engagement Scale within the context of local administration in Suphanburi, Thailand, using Covariance-Based Structural Equation Modeling (CB-SEM) via SmartPLS software. The principal aim is to determine the scale’s dimensional structure and reliability, providing insights into its effectiveness for measuring employee engagement in the local government sector. The research involved a sample of 204 officials from local government organizations, selected via simple random sampling. A questionnaire comprising three main dimensions of employee engagement (intellectual, social, and affective engagement) was employed for data collection. The CB-SEM results indicated robust model fit indices: a chi-square (χ2) value of 71.683 (p < 0.001), a chi-square/df ratio of 2.987, a Goodness-of-Fit Index (GFI) of 0.930, a Comparative Fit Index (CFI) of 0.948, a Tucker Lewis Index (TLI) of 0.923, a Normed Fit Index (NFI) of 0.925, and a Root Mean Square Error of Approximation (RMSEA) of 0.099. Despite the chi-square statistic indicating a poor fit, the other indices suggest the model’s robustness and acceptability. The study’s findings confirm the questionnaire’s validity and reliability for the specified population, endorsing its use as a research instrument in this field.